2002
DOI: 10.2298/zmspn0201029v
|View full text |Cite
|
Sign up to set email alerts
|

Transferring of Sclerotinia resistance from wild into cultivated sunflower: Combining of conventional and laboratory techniques

Abstract: Five populations of each H. molis, H. maximiliani, H. rigidus and H. tuberosus were screened for resistance to stem form of Sclerotinia. On the basis of the results obtained by screening, nine crosses of resistant populations with either other wild species populations or with cultivated sunflower were made. As in some crosses a small quantity of seed was produced and the seeds germinated poorly, modified tissue culture methods were used to enhance germination and produce clones of interesting plants. These met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…It is known that naphthenic acid can also act as a regulators of plant growth (Parups, 1969), which has been confirmed in our previous works, reporting that mixtures of natural naphthenic acids isolated from middle and higher fractions of the Vojvodina crude oil "Velebit" exhibited physiological activity analogous to that of plant hormones of auxin and gibberellin type (Ćirin-Novta et al, 2002;Vasić et al, 2002).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is known that naphthenic acid can also act as a regulators of plant growth (Parups, 1969), which has been confirmed in our previous works, reporting that mixtures of natural naphthenic acids isolated from middle and higher fractions of the Vojvodina crude oil "Velebit" exhibited physiological activity analogous to that of plant hormones of auxin and gibberellin type (Ćirin-Novta et al, 2002;Vasić et al, 2002).…”
Section: Introductionsupporting
confidence: 60%
“…Most probably, the mixture of naphthenic acids obtained from these fraction (which is characterized by a mass ratio of C atoms in cyclic structures of 62.1%, in aliphatic structures 33.7% and in aromatic structures of 4.4%, with an average number of C atoms in a molecule being 15 and average molar mass of 243) has a favorable composition that stimulates root formation. The obtained results are of great practical importance as naphthenic acids could be used for this purpose, which has been the subject of a pending patent (Kevrešan et al, 2002).…”
Section: Resultsmentioning
confidence: 88%
“…Accessions of Helianthus mollis, Helianthus rigidus and Helianthus tuberosus, originating from the wild sunflower species collection of Institute of Field and Vegetable Crops, Novi Sad, Serbia, were used in the study (Table 1). The accessions were pre-screened for their tolerance to mid-stalk white rot following the protocol of Vasić et al (2002).…”
Section: Methodsmentioning
confidence: 99%
“…Wild Helianthus species constitute a useful source of genes responsible for resistance to pathogens (Georgieva-Todorova, 1976), including Sclerotinia. Škorić and Rajčan (1992) and Henn et al (1997) found the highest level of resistance to Sclerotinia stem infection in Helianthus maximiliani accessions, while Vasić et al (2002) detected the highest level of resistance to the same infection in accessions of Helianthus mollis.…”
Section: Introductionmentioning
confidence: 97%